Effects Of Human Capital And Technology Oneconomic Growth In The Asean Region - M. Hafidz Farhan Fauzi (Epistemik Press, 2020)
Fast and quality economic growth can be achieved with the following factors:increase in capital accumulation, and human resources. Today, many countries areadapt to the acceleration of domestic production by utilizing the role oftechnology. This study aims to see the impact of the influence of human capital andthe role of technology on economic growth by taking a theoretical approachneoclassical and new growth . The method used is using panel data from 10ASEAN member countries in the period 1971-2017. The main variables in this studyare human capital and technology, by including other variables such as growthpopulation, capital growth and depreciation as control variables. The results of this studyshows that of all variables show a significant effect oneconomic growth in the ASEAN region, while the feasibility of the model showsthat the new growth model approach is better than the neoclassical model whichshown by the coefficient of determination of 87% in the new growth model and 21% inneoclassical model.